Penilaian kompetensi guru SMA dalam bidang pendidikan jasmani, olahraga, dan kesehatan sebagai keterampilan dalam melaksanakan tugas. - Haris Fauzi; Akhmad Sobarna; Muchamad Muchamad; Heni Yuli Handayani; Septyaningrum Putri Purwoto (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
The quality of learning and achievement of educational goals at Senior High School depend on PE teachers' competency. Because it is comprehensive and systematic, the CIPP (Context, Input, Process, Product) model should be used to evaluate PE teachers at Bogor Regency Senior High Schools. This research was quantitative. Evaluation gathers data for this project. The Context, Input, Process, and Product (CIPP) paradigm is used to evaluate Bogor Regency senior high school physical education, sports, and health educators. This research employed purposive sampling to choose high school instructors in Bogor Regency, state school teachers, accredited teachers, and Physical Education, Sports, and Health teachers. Based on the sampling method and criteria, this study used 28 samples. Data was gathered through various methods, including observation, interviews, surveys, and document review. The data analysis used is a percentage. The findings CIPP revealed that the Pedagogical Competence: 75% in the Content aspect (good), 81% in the Input aspect (very good), 77% in the Process aspect (good), and 75% in the Product aspect (good). For Professional Competence, the Context aspect scored 76%, Input 77%, Process 73%, and Product 72%. The conclusion obtained in this study is that the Competence of public elementary school physical education and health teachers in Bogor Regency is in a good category. Based on this research, the recommendation is that broader research on teacher competency evaluation using the CIPP model for all teachers in Bogor Regency needs to be conducted.